The theory of tragedy in Germany around 1800: a genealogy of the tragic - Billings, J (2011)
The thesis focuses on the theory of tragedy in Germany around 1800, and has two primary aims: to demonstrate the importance of idealist thought for contemporary approaches to tragedy and the tragic; and to revise the intellectual historiography of the classic phase in German letters. It traces reflection on Greek tragedy from the Querelle des anciens et des modernes in France around 1700 through the aesthetic systems formulated in Germany around 1800. Two intellectual developments are emphasized: the historicist consciousness that develops throughout the eighteenth century and places Greek tragedy more radically in its cultural context than ever before; and the idealist philosophy of art, which seeks to restore a measure of universality to the ancient genre, seeing it as the manifestation of a timeless quality of ‘the tragic.’ These two impulses, historicizing and universalizing, it is argued, are fundamental to modern understanding of Greek tragedy. The genealogical method seeks to establish a greater continuity with earlier eighteenth-century thought than is generally recognized, and to refute the teleologies that dominate accounts of idealist thought. A reconstruction of the central texts of Schiller, Schelling, Hegel, and Hölderlin reveals that the theory of tragedy around 1800 is in large part a reflection on history, an effort to understand how ancient literature can be meaningful in modernity. Greek tragedy becomes the ground for an engagement with the pastness of antiquity and its possible presence. Idealist theories, far from dissolving particularity in abstraction, seek a mediation between philological historicism and philosophical universalism in considering Greek tragedy. A genealogy of the tragic suggests that such mediation remains a vital task for scholars of the Classics.